On Some Ve-Degree and Harmonic Molecular Topological Properties of Carborundum - Cancan, Murat; Yamaç, Kerem; Taş, Ziyattin; Aldemir, Mehmet Şerif (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
Carborundum, also known as silicon carbide which containing carbon and silicon, is a semiconductor. Molecular topological properties of physical substances are important tools to investigate the underlying topology of these substances. Ev-degree and ve-degree based on the molecular topological indices have been defined as parallel to their corresponding classical degree based topological indices in chemical graph theory. Classical degree based topological properties of carborundum have been investigated recently. As a continuation of these studies, in this study, we compute novel ve-degree harmonic, ve-degree sum-connectivity, ve-degree geometric-arithmetic, and ve-degree atom-bond connectivity, the first and the fifth harmonic molecular topological indices of two carborundum structures.